Extravagant Abjection : Blackness, Power, and Sexuality in the African American Literary Imagination. - Scott, Darieck (Sexual cultures., 2010)
Challenging the conception of empowerment associated with the Black Power Movement and its political and intellectual legacies in the present, Darieck Scott contends that power can be found not only in martial resistance, but, surprisingly, where the black body has been inflicted with harm or humiliation. Theorizing the relation between blackness and abjection by foregrounding often neglected depictions of the sexual exploitation and humiliation of men in works by James Weldon Johnson, Toni Morrison, Amiri Baraka, and Samuel R. Delany, Extravagant Abjection asks: If we're racialized through do.